The Relationship Between Patient Satisfaction in Independent Dental Practices and the Rate of Repeat Visits in Cikoko Pancoran: Indonesia - Hayana, Nanda Bella; Hastono, Sutanto Priyo (VISIKES, 2025)
The level of patient satisfaction can influence revisit behavior, which in turn is related to the sustainability of practice and the improvement of healthcare service quality. This study aims to determine the relationship between patient satisfaction and revisit rates in private dental practices and to analyze healthcare service quality based on the five dimensions of healthcare service quality in private dental practices. This research employs a cross-sectional design. The sample was selected using convenience sampling. The research method used is a mixed method with an explanatory sequential design. The quantitative approach was conducted first to measure the level of patient satisfaction and the number of patient visits, followed by a qualitative approach to explain the quantitative findings, particularly the factors influencing patient satisfaction. The analysis was performed using the chi-square test to examine the relationship between patient satisfaction and revisit rates. The study found a significant link between patient satisfaction and revisit rates ($p < 0.05$). Highly satisfied patients were more likely to return. Thus, patient satisfaction is key to increasing revisit rates and improving service quality and patient loyalty in private dental practices.